Pengaruh Diorama Pemindaian Kode Batang terhadap Keterampilan Proyek Siswa dalam Pembelajaran Sains untuk Siswa Kelas IV di Sanggar Belajar Kepong Malaysia - Tania, Dinda; Nasution, Ismail Saleh (Jurnal Gentala Pendidikan Dasar, 2026)
Technology in elementary schools is increasingly needed to provide an interesting, meaningful, and modern learning experience. This research examines how integrating barcode scanning with diorama media influences the project skills of fourth-grade students at SB Kepong, Malaysia. Diorama media combined with barcode scans is designed to provide fast and interactive access to additional information, so that students can explore the material in more depth. A quasi-experimental quantitative design with a pretest and posttest control format was applied in this study. The research involved nine fourth-grade students who were organized into two groups. The experimental group learned through diorama media integrated with barcode scanning, while the control group participated in conventional classroom learning. Data collection was carried out using observation sheets to measure students’ project skills and questionnaires to capture students’ learning responses. The findings revealed that the mean pretest score was 20.2%, which later increased to 46% in the posttest. The Wilcoxon Signed-Rank Test yielded a significance value of 0.007, which is below 0.05, indicating a significant difference between the pretest and posttest scores. These results suggest that the use of Barcode Scan Diorama as a learning medium significantly enhances students’ interest in science at the Muhammadiyah Kepong Malaysia Guidance Center.